Design of Windows-Based Learning Applications on Educational Philosophy Material - Syahputra, Fahmy; Putri, Tansa Trisna Astono; Barus, Tirta Yasa Agung; Jauharah, Jauharah; Tarigan, Febrinata Silvinna Boru; Sinaga, Novi Novani (CV. Rayyan Dwi Bharata, 2024)
This journal discusses the design and development of Windows-based learning applications focused on educational philosophy material. Philosophy of education has an important role in shaping the goals and methods of education, but is often considered difficult by students. This research focuses on the development of a Windows-based learning application aimed at the topic of Philosophy of Education. Information technology is essential for teaching in the modern era to improve student interaction and their understanding of the subject matter. Students can learn the basic concepts of philosophy of education with this interactive application. Planning, modeling, construction, verification, and maintenance are the stages of the waterfall model used as the development method. This application uses Visual Basic.Net and Microsoft Visual Studio development tools. The results show that this application not only fulfills educational needs but also improves the quality of learning because it has features that support a more dynamic learning process. Therefore, it is expected that this learning application will help improve the quality of education in Indonesia by offering students a more efficient and engaging learning method.